The Sunken Billions Revisited : Progress and Challenges in Global Marine Fisheries - World Bank (Washington, DC: World Bank, 2016)
Global marine fisheries are in crisis: 90 percent are fully fished and overfished. The result is lost economic benefits of approximately $83 billion a year ---the “sunken billions” of the title. Reducing overfishing would allow severely overexploited fish stocks to recover over time. Subsequently, the combination of larger fish stocks and reduced but sustainable fishing activities would lead to higher economic yields. However, to reach that equilibrium, comprehensive and coordinated reforms are necessary. The Sunken Billions Revisited: Progress and Challenges in Global Marine Fisheries builds on The Sunken Billions: The Economic Justification for Fisheries Reform, a 2009 study published by the World Bank and Food and Agriculture Organization of the United Nations, but with a deeper regional analysis.